Transnational mobility, strong states and contested sovereignty: learning from the China–Taiwan context - Momesso, Lara; Lee, Chun-Yi (SAGE Publications, 2017)
Mobility across the Taiwan Strait has intensified since the border was opened in 1987. The cross-border social, cultural and economic exchanges, however, have remained closely embedded in the nationalistic logic specific to cross-Strait relations. Employing a state-centered approach and building on a comparative analysis of the interaction between Beijing and two groups of cross-Strait migrants (mainland spouses in Taiwan, and Taiwanese investors in China), this paper examines the various ways in which a state may still exert influence over migrant communities in a context of increased mobility and exchanges. This paper argues that the nation-state may still shape migrants’ experiences, particularly when sending and receiving governments have unresolved disputes. Under these conditions, state actors may use migrant communities to achieve their nationalistic goals.